Family Gathering After Memorial Service For Esther Fine - Watkins, Howard::::::::: (1982)
Seated: ?, David Gomez, ? ?? Dorene Gomez; Standing: ? Lopez, David Lopez, Marsha Lopez, ?, Lorraine, ????Albert Watkins, Rose Watkins,?? Lois Rivera, Dawn Gomez, Linda Gomez/, Adam Watkins, Christine Watkins, Howard Watkins, ?, ?